Coupling effects of boron nitride and heat treatment on crystallization, mechanical properties of poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV). (14th June 2022) - Miao, Yushuang; Fang, Chenxia; Shi, Dan; Li, Yiguo; Wang, Zongbao
Abstract: The coupling effects of boron nitride (BN) addition and the heat treatment of partial melt recrystallization method (PMRM) on the crystallization and mechanical properties of poly (3-hydrox ybutyric- co -3-hydroxyvaleric acid) (PHBV) were investigated by DSC, mechanical properties tests, WAXD and SAXS measurements. The addition of BN could significantly increase the nucleation density and cold crystallization temperature, thus substantially increasing the crystallization rate of PHBV. The heat treatment of PMRM was proved to be an effective method to improve the mechanical properties of PHBV, it can rearrange the molecular chain of PHBV, causing the HV chain segments to discharge the lattice of poly (3-hydroxybutyrate) (PHB), promoting the uniform distribution of amorphous layers, and reducing the entanglement of molecular chains, contributing to an improvement of the toughness of PHBV and PHBV/BN composites. The coupling effect occurred between the addition of BN and the heat treatment, for which the BN addition can not only improve the toughness of PHBV, but also enormously increase the crystallization rate during heat treatment, so as to significantly shorten the time required for heat treatment and effectively solve the disadvantage of slow crystallization at high temperature. Graphical abstract: Image 1 Highlights: BN addition increased the cold crystallization temperature and the crystallization rate of PHBV. The heat treatment of PMRM can effectively improve the mechanical property of PHBV. BN addition toughened PHBV and increased the crystallization rate of heat treatment. BN addition shortened the time required for heat treatment.